HUBUNGAN KEMAMPUAN KOMUNIKASI MATEMATIS DAN RESILIENSI MATEMATIS SISWA SEKOLAH MENENGAH ATAS - Vika Rosa; Halini Halini; Hamdani Hamdani (Jurnal AlphaEuclidEdu, 2021)
This research aimed to describe mathematical communication skills, mathematical resilience, and the relationship between mathematical communication skills and mathematical resilience. This research used a quantitative approach with a correlation research design. The population in this study were students of grade XI SMA Negeri 2 Teluk Keramat and the sample was students of grade XI MIPA 2.The results showed that the mathematical communication skills students tend to have is the ability to express mathematical concepts by stating daily events in language or mathematical symbols (mathematical expression ability) which were able to be achieved by the students as much as 62%. Whereas for mathematical resilience that students tend to have is to have curiosity, reflect, research, and make use of various sources in mathematics learning, which contributed 38.7% and were able to be achieved by 16 students (76%). Furthermore, based on the results of the Pearson Product Moment correlation test, a significance value of 0.021 and a correlation value of 0.500 was obtained. So it can be concluded that there is a significant relationship between mathematical communication skills, mathematical resilience, and the strength of the correlation between the two variables is classified as moderate. Keywords: Correlation, Mathematical Communication Skills, Mathematical Resilience